Pigmentary traits, sun exposure, and risk of non‐Hodgkin's lymphoma/chronic lymphocytic leukemia: A study within the French E3N prospective cohort. (21st November 2020) - Garcin, Louis‐Marie; Gelot, Amandine; Gomez, Roselyn‐Rima; Gusto, Gaëlle; Boutron‐Ruault, Marie‐Christine; Kvaskoff, Marina; Severi, Gianluca; Besson, Caroline
Abstract: To investigate whether risk factors for keratinocyte carcinomas (KCs), namely pigmentary traits and sun exposure, are associated with risk of non‐Hodgkin's lymphomas (NHL) and chronic lymphocytic leukemia (CLL). E3N is a prospective cohort of French women aged 40–65 years at inclusion in 1990. Cancer data were collected at baseline and updated every 2–3 years. Hazard Ratios (HRs) and 95% confidence intervals (CIs) for associations between pigmentary traits and sun exposure,  and risk of CLL/NHL were estimated using Cox models. With a median follow‐up of 24 years, 622 incident cases of CLL/NHL were ascertained among the 92, 097 included women. The presence of nevi was associated with CLL/NHL risk: HR for "many or very many nevi" relative to "no nevi": 1.56 [1.15; 2.11]. Such association with number of nevi appears to be mostly limited to risk of CLL: HR for "many or very many nevi": 3.00 [1.38; 6.52]; versus 1.32 [0.94; 1.84] for NHL. Women whose skin was highly sensitive to sunburn also had a higher risk of CLL: HR = 1.96 [1.21; 3.18], while no increase in risk of NHL was observed. Skin or hair color, number of freckles, and average daily ultraviolet (UV) dose during spring and summer in location of residence at birth or at inclusion (kJ/m 2 ) were not associated with CLL/NHL risk. Some pigmentary traits (presence of nevi and skin sensitivity),  but not sun exposure, were associated with CLL/NHL. These observations suggest that CLL may share some constitutional risk factors with keratinocyte cancers. Abstract : We investigated whether keratinocyte carcinomas risk factors were associated with Chronic lymphocytic leukemia (CLL) and non‐Hodgkin's lymphoma (NHL) risk. We report an association between risk of CLL/NHL and number of nevi. Our findings suggest a partially common genetic etiology of these tumors instead of shared environmental risk factors.